Efektifitas Panduan Praktikum GLBB Berbasis Outcome-Based Education untuk Meningkatkan Keterampilan Praktis Mahasiswa Pendidikan Fisika: outcome-based education, practicum guide, practical skills. - Hanifah Zakiya; Ryna Aulia Falamy (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
The process of developing Outcome Base Education (OBE) oriented student skills is formed through practicum activities that focus on mapping competencies that can improve students' practical skills. This research focuses on developing or refining a practicum guide for Regularly Changing Straight Motion (GLBB) that has been integrated with OBE-oriented practical skill competencies. This practicum guide was developed using the ADDIE Model method which consists of needs analysis, design, development, implementation and evaluation. The instrument used is a validation sheet for the development of practicum guides and questionnaires for users. The results showed that the OBE-based practicum guide proved effective in improving students' practical skills with moderate effect qualifications. A total of 89.05% of first-year physics education students strongly agreed that the OBE-oriented practicum guide in improving their practical skills. Indicators of practical skills as outcomes that can be trained to students through this practicum activity are skills in using laboratory equipment and techniques, being able to analyze experimental data and draw logical conclusions, being able to convey experimental results effectively, and being able to identify problems and their solutions.